2018
DOI: 10.1007/s00198-018-4721-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor is a potential biomarker for osteoproliferation and osteoporosis in ankylosing spondylitis

Abstract: Summary We explored relations between serum hepatocyte growth factor (HGF), disease activity, osteoproliferation, and bone mineral density (BMD) in ankylosing spondylitis (AS), in comparison with healthy controls. HGF was increased especially in male AS patients and smokers and associated with both lower BMD and more chronic radiographic changes in the spine. Introduction Ankylosing spondylitis (AS) is characterized by both osteoproliferation and increased bone loss. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…All other correlations tested between biomarkers in this panel and MRI inflammation in the spine yielded insignificant relationships. Two reports have recently described cross-sectional associations between hepatocyte growth factor (HGF) and acute phase reactants ( 17 , 18 ). HGF is secreted by mesenchymal cells and has pleiotropic effects that include suppression of inflammation and enhanced osteoblastic differentiation of mesenchymal cells.…”
Section: Disease Activity Biomarkersmentioning
confidence: 99%
“…All other correlations tested between biomarkers in this panel and MRI inflammation in the spine yielded insignificant relationships. Two reports have recently described cross-sectional associations between hepatocyte growth factor (HGF) and acute phase reactants ( 17 , 18 ). HGF is secreted by mesenchymal cells and has pleiotropic effects that include suppression of inflammation and enhanced osteoblastic differentiation of mesenchymal cells.…”
Section: Disease Activity Biomarkersmentioning
confidence: 99%
“…Also, an increased average s-HGF was associated with development of new syndesmophytes in men. s-HGF in relation to AS-related spinal alterations has, to our knowledge, only been evaluated before in our baseline, cross-sectional study, which demonstrated that higher s-HGF was associated with higher mSASSS [ 15 ]. The pathophysiological mechanisms behind the relationship between new bone formation and HGF in AS are not known, but there are several possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that serum HGF (s-HGF) was higher in patients with AS than in controls and independently associated with higher modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) [ 15 ]. The aims of the present study were to assess (i) baseline s-HGF as a predictor for spinal radiographic progression over 5 years overall and by sex, and (ii) if demographic characteristics, disease activity and medications are correlated with changes in s-HGF.…”
Section: Introductionmentioning
confidence: 99%
“…The role of HGF was also proven in the progression of AS. L. Torres et al [ 247 ] demonstrated higher levels of HGF in the serum of AS patients compared to healthy donors, which directly correlated with the disease activity and inversely correlated with the level of BMD. This observation demonstrates the importance of this cytokine in diagnostics and treatment of AS and osteoporosis as a frequent AS complication.…”
Section: Aptamers For Protein Biomarkers Of Rheumatic Disordersmentioning
confidence: 99%